Apropriação do conceito de célula por estudantes de escolas públicas de Santa Maria, RS, a partir de uma ferramenta pedagógica - Garcia, Janisse Viero (2013)
Understanding how students elaborate the concepts during the school trajectory is an important tool in the teaching learning process, since they can assist the design and planning of learning activities. In this context, taking into account that the cell is a key concept in the biological sciences, this study aimed to understand how students elaborate the concept of cell in their trajectory, using as collateral the comic "Lung and Her Crew", and propose actions that can be used in basic education contributing to more effective development of the concept of cells and Science Teaching. The study was conducted with students from elementary and middle schools in two public schools in Santa Maria, RS. For data collection semi-structured questionnaires to evaluate the use of the comic book "Lung and his gang," as a pedagogical tool for students were used, and semi-structured interviews to understand how students elaborate the concept of cell and if there is increased complexity of cell concept reported by students throughout the school year. In the analysis of the interviews sought to identify the methods of generalization of the concept, establishing categories based on the stages of development of the concepts developed by Vygotsky. From the survey data we proposed educational activities that can contribute to a more effective development of the concept of cells and Science Teaching. The results obtained in this study revealed that for the question of the cells, the high school students are those who have had some notion of the concept of cells. We note that, although students may have an idea about what they say, the real complexity of the issue probably was not perceived in its entirety by the student and should not be incorporated into their cognitive structure. However, we should point out that the concept can be merely discursive without an actual of what the subject conceptualized reflection. These results reinforce the idea that the description, whether written or verbal, that cells are the morphological and microscopic units that make up living things, can not pass a speech with little cognitive or scientific significance. That is, cell, gene, chromosome "are things of biology" that are related to life, but rather precisely within the cognitive structure of the students.